Penguatan Brand Image melalui Digital Marketing dalam Mendorong Keputusan Pembelian UMKM Lokal - Raden Roro Gustiani; Asmi Ayuning Hidayah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The rapid growth of digital technology has significantly transformed marketing strategies among MSMEs in Indonesia. Social media and e-commerce platforms are no longer merely promotional tools but also play a crucial role in shaping consumer perceptions of brands. This study aimed to examine the effect of digital marketing on purchase decisions with brand image as a mediating variable among MSMEs. A quantitative approach was employed using a survey of 144 MSME consumers in Purwokerto who had interacted with digital promotions. Data were analyzed using Structural Equation Modeling (SEM). The findings revealed that digital marketing had a positive and significant effect on both brand image and purchase decisions. Furthermore, brand image partially mediated the relationship between digital marketing and purchase decisions, indicating that consumers evaluate brand perceptions before making purchasing decisions. These results highlight the importance of strengthening digital marketing strategies to build a positive brand image and enhance MSME competitiveness in the digital era. Keywords: brand image; digital marketing; MSMEs; purchase decision